2018
DOI: 10.1177/0269215518801430
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of backward walking as a treatment for people with gait impairments: a systematic review and meta-analysis

Abstract: The systematic review and meta-analysis suggests that backward walking with conventional physiotherapy treatment is effective and clinically worthwhile in patients with knee osteoarthritis. Insufficient evidence was available for the remaining gait impairment conditions and no conclusions could be drawn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 36 publications
(110 reference statements)
0
13
0
Order By: Relevance
“…Backward walking (BW) is an activity with additional complexity compared to regular forward walking (FW). Although some studies have shown that BW is a mirror image of FW, considering that initial contact during BW is done by the toe instead of the heel 17 , 18 . BW differs from FW in many aspects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Backward walking (BW) is an activity with additional complexity compared to regular forward walking (FW). Although some studies have shown that BW is a mirror image of FW, considering that initial contact during BW is done by the toe instead of the heel 17 , 18 . BW differs from FW in many aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, BW offer a unique challenge to balance and movement. Thus, BW is used increasingly in rehabilitation programs to promote balance control 17 .…”
mentioning
confidence: 99%
“…One systematic review was dedicated to the hand 70 ; and two were dedicated to diet 14,71 . The remaining focused on exercise 18,72e77 , including aquatic 78 and gait 79 . AMSTAR 2 scores were critically low (n ¼ 4), low (n ¼ 4), moderate (n ¼ 3) and high (n ¼ 2).…”
Section: Synthesis Papersmentioning
confidence: 99%
“…e latest meta-analysis [21] showed that BW, as an adjunctive therapy, with conventional treatment was effective and worth to promote in patients with KOA. Furthermore, current evidence reveals that it had been considered as a potential strategy to improve balance performance and prevent falling for health subjects [22] and the people suffering from stroke [23], or cerebral palsy [24].…”
Section: Introductionmentioning
confidence: 99%